FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Arief Nurhandika; Faishal Rahimi (UIN Sunan Gunung Djati Bandung, 2020)
The purpose of this study is to find out empirically evidence of the effects of resource looseness, the mechanism of corporate governance that is proxied, among others, the composition of the board of commissioners, managerial ownership, foreign ownership of the audit committee and the size of the public accounting firm's office on the quality of disclosure. The population in this study is all manufacturing companies and purposive sampling methods used in determining the sample so that 35 companies were obtained from 2013 to 2017. The results showed that: (1) resource looseness has a positive influence on the quality of social responsibility disclosure, (2) the composition of the board of commissioners does not affect the quality of social responsibility disclosure (3) managerial ownership does not affect the quality of social responsibility disclosure (4) foreign ownership does not affect the quality of social responsibility disclosure (5) the audit committee does not affect the quality of social responsibility disclosures, (6) the public accounting firm influences the quality of social responsibility disclosure.Keywords: Slack Resource, Board of Commissioners Composition, Managerial Ownership, Foreign Ownership, Audit Committee, Public Accounting Firm, Quality of Social Responsibility Disclosures.